2021
DOI: 10.3389/fcell.2021.715883
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Hexokinase 2 Immune Infiltrates and m6A Related Genes in Human Esophageal Carcinoma

Abstract: Background: Hexokinase 2 not only plays a role in physiological function of human normal tissues and organs, but also plays a vital role in the process of glycolysis of tumor cells. However, there are few comprehensive studies on HK2 in esophageal carcinoma (ESCA) needs further study.Methods: Oncomine, Tumor Immune Estimation Resource (TIMER), The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) database were used to analyze the expression differences of HK2 in Pan-cancer and ESCA cohort, and to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…So far as the present conclusions are concerned, the differences in the correlation between the three separate scores might depict a conceptual map formed by immune and stromal cells in various malignancies, thus explaining the differential role of NCAPG2 in the prognosis of patients with diverse tumors. Targeting immune checkpoint genes like PD-1 and PD-L1, immune checkpoint blockade is currently among the mainstream immunotherapies (47,48). The present study found that NCAPG2 displayed a significant correlation with ICI-related genes in most cancers, with a predominantly positive correlation.…”
Section: Discussionsupporting
confidence: 50%
“…So far as the present conclusions are concerned, the differences in the correlation between the three separate scores might depict a conceptual map formed by immune and stromal cells in various malignancies, thus explaining the differential role of NCAPG2 in the prognosis of patients with diverse tumors. Targeting immune checkpoint genes like PD-1 and PD-L1, immune checkpoint blockade is currently among the mainstream immunotherapies (47,48). The present study found that NCAPG2 displayed a significant correlation with ICI-related genes in most cancers, with a predominantly positive correlation.…”
Section: Discussionsupporting
confidence: 50%
“…The signi cant association between HK2 and T cells have been con rmed by several studies. For example HK2 is involved in tumor immune in ltration and m6A modi cation in ESCA [32]. It is noteworthy that HK3 also has the strongest correlation with tumor immunity, indicating that HK3 may serve as a new marker of tumor immunity.…”
Section: Discussionmentioning
confidence: 97%
“…And, abnormal glycosylation is also considered an indispensable part of the carcinogenesis process ( Ni et al, 2014 ), including BLCA. The research on protein modification and tumor heterogeneity, as well as the prediction of immunotherapy efficacy such as ICB, remains a hot topic in many cancers ( Liu et al, 2021 ; Liu et al, 2022 ). Therefore, our research was dedicated to deeply exploring the association between glycosylation and BLCA, with the goal of accurately predicting prognosis and individualized guidance for treatment of BLCA.…”
Section: Discussionmentioning
confidence: 99%